THE IMPORTANCE OF ENGLISH FOR PROFESSIONAL DEVELOPMENT IN TECHNICAL FIELDS. - Madumarova Mohinur, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  In  today’s  globalized  world,  English  serves  as  the  universal language of technology, science, and innovation. Professionals in technical fields—such  as  engineering,  information  technology,  and  applied  sciences—need  English proficiency to access up-to-date information, participate in international collaboration, and present their research globally. This article examines the importance of English for professional development in technical fields, analyzing relevant literature, methods of language  integration  in  professional  education,  and  the  outcomes  of  English-based training programs.